2008
DOI: 10.1016/j.juro.2008.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Prospective Comparative Analysis of Outcomes Between Open and Laparoscopic Radical Prostatectomy Conducted in 2003 to 2005

Abstract: At our institution and during the study period laparoscopic radical prostatectomy and retropubic radical prostatectomy provided comparable oncological efficacy. Laparoscopic radical prostatectomy was associated with less blood loss and a lower transfusion rate, and higher postoperative hospital visits and readmission rate. While the recovery of potency was equivalent, that of continence was superior after retropubic radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 19 publications
10
80
0
10
Order By: Relevance
“…Two recent meta-analyses of studies that directly compared RRP, LRP, and RARP confirmed that RARP is associated with decreased operative blood loss and decreased risk of transfusion 13,14 It is noteworthy to mention, however, that some transfusion rates reported in RRP series are significantly biased by autologous blood transfusion protocols, which have a clearly more liberal indication for transfusion during the procedure. 33 The mean in-hospital stay was higher for LRP series than in RRP and RARP in our review (4.87, 3.48, and 1.43 days, respectively). These results, however, probably reflected the differences in the location where the series were carried out.…”
Section: Perioperative Outcomesmentioning
confidence: 51%
See 3 more Smart Citations
“…Two recent meta-analyses of studies that directly compared RRP, LRP, and RARP confirmed that RARP is associated with decreased operative blood loss and decreased risk of transfusion 13,14 It is noteworthy to mention, however, that some transfusion rates reported in RRP series are significantly biased by autologous blood transfusion protocols, which have a clearly more liberal indication for transfusion during the procedure. 33 The mean in-hospital stay was higher for LRP series than in RRP and RARP in our review (4.87, 3.48, and 1.43 days, respectively). These results, however, probably reflected the differences in the location where the series were carried out.…”
Section: Perioperative Outcomesmentioning
confidence: 51%
“…The pathologic stage and PSM rates for open, RLP, and RARP series are summarized on Table 4, 16-22,24-28,30,31,33,55-57 Table 5, 33,37,38,[40][41][42][44][45][46][47] and Table 6, 30,31,35,[48][49][50][51][52][53][54]58 respectively. The pathologic stage in the RARP series was of 78.2% pT 2 tumors and 20.5% pT 3 tumors.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in Europe, interest in LRP continued and the procedure enjoyed a new wave of popularity following the work by Guillonneau et al [4] in 1999. Outcome data from centres of excellence showed cancer control rates, urinary continence and potency rates comparable to those of ORP, but with the additional benefit to patients of a minimally invasive approach [5,6]. However, LRP is a difficult procedure with a long learning curve, and concerns over this and long-term oncologic efficacy resulted in poor uptake of this procedure, particularly in the United States.…”
Section: Evolution Of Ralrp From 2000 To 2009mentioning
confidence: 99%